An analytical study of the facts of the use of steroids in sports under the regime of globalization - Hadi Gary, Aseer (Journal of Physical Education, 2012)
Section One contains the importance of research in terms of a system of globalization the world and its effects on sports stadiums in all disciplines and sports competitions Among the manifestations of globalization sports is the use of steroids sports by a lot of players, either in Part II has contained Identification of globalization and globalization sports and the definition of doping historical background and give them then explained their effects on the players and their use in sports stadiums, and in Part III, which included the research methodology and procedures in terms of the sample field of research and exploratory experience and tools used in this research as well as the most important statistical methods .In Part Four was viewing the results and discussion obtained by the researcher through the standard deviations and circles arithmetic and percentages, which indicated that the Nazism of globalization basic role in the dissemination of mathematical concepts of good and Ethics Commissioner that contrary to the use of steroids sports, and in section Vhas been the most important conclusions and recommendations reached by the researcher through the research